Silk fibroin and sericin polymer blends for sustainable battery separators - Reizabal, A. (2022)
Natural polymers are a promising alternative for reducing the environmental impact of batteries. For this reason, it is still necessary to study their behavior and implement its use in these devices, especially in separator membranes. This work reports on new separator membranes based on silk fibroin (SF) and silk sericin (SS) prepared by salt leaching method. The effect of the different SS relative content on the physiochemical properties of the membranes and on the electrochemical performance of the corresponding batteries with lithium iron phosphate (LFP) as cathodes has been reported. It is observed that the increasing of SS content leads to a decrease of the overall crystallinity of the membranes. All SF/SS membranes presented a well-defined porosity above 75% with a uniform distribution of interconnected micropores. The electrolyte uptake and the ionic conductivity are dependent on the relative SS content. The addition of 10 wt% of SS into SF membranes, induce a high ionic conductivity of 4.09 mS.cm−1 and high lithium transference number (0.52), due to the improvement of the Li+ ions conduction paths within the blended structure. Charge/discharge tests performed in Lithium/C-LFP half-cells reveal a discharge capacity of 85 mAh.g−1 at 2C after 100 cycles for batteries with a SF/SS separator, containing a 10 wt% of SS, which suggests a stabilizing effect of Sericin on discharge capacity. Further, a 50% and 35% of capacity of retention and capacity fade, respectively, is observed. The presented SF/SS membrane show high electrochemical stability, being suitable for implementation in a next generation of sustainable battery systems. This could allow the SS valorization considering that 150,000 tons of SS are abandoned each year, reducing the contamination of environmental effluents.